Only Extreme Fluctuations in Light Levels Reduce Lettuce Growth Under Sole Source Lighting - Bhuiyan, Ruqayah; van Iersel, Marc W. (Frontiers in Plant Science, 2021)
The cost of providing lighting in greenhouses and plant factories can be high. In the case of variable electricity prices, providing most of the light when electricity prices are low can reduce costs. However, it is not clear how plants respond to the resulting fluctuating light levels. We hypothesized that plants that receive a constant photosynthetic photon flux density (PPFD) will produce more biomass than those grown under fluctuating light levels. To understand potential growth reductions caused by fluctuating light levels, we quantified the effects of fluctuating PPFD on the photosynthetic physiology, morphology, and growth of ‘Little Gem’ and ‘Green Salad Bowl’ lettuce. Plants were grown in a growth chamber with dimmable white LED bars, alternating between high and low PPFDs every 15 minutes. The PPFDs were ~ 400/0, 360/40, 320/80, 280/120, 240/160, and 200/200 µmol·m-2·s-1, with a photoperiod of 16 hours and a DLI of ~11.5 mol·m-2·d-1 in all treatments. CO2 was ~ 800 µmol·mol-1. Plants in the 400/0 µmol·m-2·s-1 treatment had ~69% lower An,30 (net assimilation averaged over 15 minutes at high and 15 minutes at low PPFD) than plants grown at a PPFD of 320/80 µmol·m-2·s-1 (or treatments with smaller PPFD fluctuations). The low An,30 in the 400/0, and to a lesser extent the 360/40 µmol·m-2·s-1 treatment was caused by low net assimilation at 360 and 400 µmol·m-2·s-1. Plants grown at 400/0 µmol·m-2·s-1 also had fewer leaves and lower chlorophyll content compared to those in other treatments. The four treatments with the smallest PPFD fluctuations produced plants with similar numbers of leaves, chlorophyll content, specific leaf area, dry mass, and leaf area. Chlorophyll content, An,30, and dry mass were positively correlated with each other. Our results show that lettuce tolerates a wide range of fluctuating PPFD without negative effects on growth and development. However, when fluctuations in PPFD are extreme (400/0 or 360/40 µmol·m-2·s-1), chlorophyll levels and An,30 are low, which can explain the low poor growth in these treatments. The ability of lettuce to tolerate a wide range of fluctuating light levels suggests that PPFD can be adjusted in response to variable electricity pricing.